Effect of ultrasonic coupling media and surface roughness on contact transfer loss. Issue 1 (31st December 2022) - Zuljan, Darjo
Abstract: The study identifies and evaluates differences in contact transfer losses with different coupling media and surface roughnesses Ra between 0.1 and 7 µm. The study was designed based on the non-destructive ultrasonic pulse-echo technique (UT) with a straight-beam probe (piezoelectric). The study is based on the findings of research that has been carried out stating that both the coupling media and surface roughness influence the results of UT tests to a considerable degree. The ultrasonic coupling media that are most commonly used in industry were selected: water, glycerine, UCA-2 M contact gel, U47 contact gel, mineral oils, and wallpaper paste. The selected coupling media have statistically significant influence on the ultrasonic contact transfer losses and thus also on testing results. It was found that the glycerine coupling media has the lowest contact transfer loss among the selected coupling media. The signal amplitude contact transfer differences were measured to establish the relative contact transfer losses. The observed variations in signal amplitude with reference to the types of coupling media and different surface roughnesses (from 0.1 to 7 μm) are higher than those reported by the International Atomic Energy Agency (IAEA) (2018). The contribution of the present study is the use of signal amplitude contact transfer differences to measure relative contact transfer losses since in this way the influence of parameters such as the type of ultrasonic apparatus, type of ultrasonic probe, temperature, and material of the specimen on our measurements was eliminated.